Interactive anatomical and surgical live stream lectures improve students' academic performance in applied clinical anatomy. Issue 1 (6th June 2016) - Shiozawa, Thomas; Butz, Benjamin; Herlan, Stephan; Kramer, Andreas; Hirt, Bernhard
Abstract : Tuebingen's Sectio Chirurgica (TSC) is an innovative, interactive, multimedia, and transdisciplinary teaching method designed to complement dissection courses. The Tuebingen's Sectio Chirurgica (TSC) allows clinical anatomy to be taught via interactive live stream surgeries moderated by an anatomist. This method aims to provide an application‐oriented approach to teaching anatomy that offers students a deeper learning experience. A cohort study was devised to determine whether students who participated in the TSC were better able to solve clinical application questions than students who did not participate. A total of 365 students participated in the dissection course during the winter term of the 2012/2013 academic year. The final examination contained 40 standard multiple‐choice (S‐MC) and 20 clinically‐applied multiple‐choice (CA‐MC) items. The CA‐MC items referred to clinical cases but could be answered solely using anatomical knowledge. Students who regularly participated in the TSC answered the CA‐MC questions significantly better than the control group (75% and 65%, respectively; P < 0.05, Mann‐Whitney U test). The groups exhibited no differences on the S‐MC questions (85% and 82.5%, respectively; P > 0.05). The CA‐MC questions had a slightly higher level of difficulty than the S‐MC questions (0.725 and 0.801, respectively; P = 0.083). The discriminatory power of the items was comparable (S‐MC median Pearson correlations: 0.321; CA‐MC: 0.283). The TSC successfully teaches the clinical application of anatomical knowledge. Students who attended the TSC in addition to the dissection course were able to answer CA‐MC questions significantly better than students who did not attend the TSC. Thus, attending the TSC in addition to the dissection course supported students' clinical learning goals. Anat Sci Educ 10: 46–52. © 2016 American Association of Anatomists.